Ytterbium-Phosphate Glass for Microstructured Fiber Laser - Stępień, Ryszard (Materials (Basel), 2014)
In the paper, we report on the development of a synthesis and melting method of phosphate glasses designed for active microstructured fiber manufacturing. Non-doped glass synthesized in a P(2)O(5)-Al(2)O(3)-BaO-ZnO-MgO-Na(2)O oxide system served as the matrix material; meanwhile, the glass was doped with 6 mol% (18 wt%) of Yb(2)O(3), as fiber core. The glasses were well-fitted in relation to optical (refractive index) and thermal proprieties (thermal expansion coefficient, rheology). The fiber with the Yb(3+)-doped core, with a wide internal photonic microstructure for a laser pump, as well as with a high relative hole size in the photonic outer air-cladding, was produced. The laser built on the basis of this fiber enabled achieving 8.07 W of output power with 20.5% slope efficiency against the launched pump power, in single-mode operation M(2) = 1.59, from a 53 cm-long cavity.